REKINDLING AND REVITALIZING JOY *NIEM V(]T, AND BEAUTY OF CONSECRATED LIFE 4OR A HOLISTiC SPIRITUAL FORMATION IN THE TRINH WJONG CONGRE,GATION, HO CHI MINH CITY, VIETNAM, IN LIGHT OF POPE FRANCIS' TEACHINGS ON JOY - NGUYEN, Hang Thi Thuy (Archīum Ateneo, 2021)
“Wherever consecrated people are, there is always joy... Joy is the beauty of consecration.” (Pope Francis, Speech, 6 July 2013) In this view, “joy is a beautiful reality in the life of many consecrated persons, but it is also a great challenge for all of us.” (Pope Francis, Speech, 22 May 2017) This study responds to the call to joy made by Pope Francis and whole people, particularly Christians, who look for witnesses of joy in the consecrated persons in this current context of more griefs and fewer joys, specifically in Vietnam. The method engaged in this project is theological reflection. In fact, the researcher is inspired to rediscover joy as the most excellent quality of the consecrated life’s beauty or attraction according to the spirituality of joy in the light of Pope Francis’ teaching contextualized in the specific situation of Trinh Vương Congregation. Acknowledging this spirituality, consecrated persons, particularly Trinh Vương sisters, can find joy in all things, so their identity, lifestyle, and mission will blossom with joy. Therefore, it is incredibly significant for this project to include a holistic spiritual formation to rekindle and revitalize joy as consecrated persons’ beauty and attraction. Both quantitative and qualitative research conducted among Trinh Vương sisters guide the design of seven-day meditation on joy expressed in various activities of Memory, Gratitude, and Charity that are sources of Marian joy inspired by the Magnificat, the song of joy. This kind of holistic spiritual formation is to help rekindle and revitalize joy in the day-to-day life of Trinh Vương sisters.